Von Recklinghausen Neurofibromatosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
A population-based study in southeast Wales and reported from the Institute of Medical Genetics and Section of Neurology, University of Wales College of Medicine, Cardiff, has identified 135 patients with neurofibromatosis type 1 (NF-1), a prevalence of approximately 1/5000.